What motivates Generation Z to travel independently? Preliminary Research of solo travellers - Suci Sandi Wachyuni; Nenny Wahyuni; Kadek Wiweka (Journal of Tourism and Economic, 2023)
Nowadays, the segmentation of solo travel in the tourism market is growing faster than other categories of travel, particularly among those classified as Generation Z. However, few studies have examined solitary travel experiences and motivation. Therefore, the purpose of this study is to determine Generation Z's motivations for solo travel. This research employs a quantitative survey method with a Likert scale and a quantitative approach. In this investigation, 30 young people participated as respondents. The technique applied to data analysis is descriptive statistical analysis. According to the findings of this study, the majority of Generation Z solo travelers are female, work as students, and have traveled solo 1-2 times. The results of the study also indicate that the primary tourist motivation for solo travel is to enjoy the destination's tourist attractions. Furthermore, they consider various factors such as value for money, looking for an inspiration, interaction with local citizens, healing purposes, the influence of social media, and self-actualization. This study's findings can be adopted by destination managers to develop recommendations for responding to the necessities of Generation Z tourists, the largest proportion of tourists at this time.